ETHNOLOGY OF THE PEOPLES OF CENTRAL ASIA (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
Ethnic composition and ethnogenesis of the Uzbek people from the earliest times to the present. Studying the ethnography of the Uzbek people. Traditional training and economic activities.